The Safe-Keeping Fee in Al-Rahn and Shariah Compliance - Jamaludin, Jeniza; Abdul Rahman, Normy Rafida; Aziz, Nur Fadhillah; Andi, Hari Krishnan (2023)
Al-Rahn is an Islamic pawn broking system introduced to help the needy and further develop the Islamic financial system in Malaysia. This Islamic mortgage system is an alternative system to conversational charge system. The Islamic institutions will charge a safe-keeping fee to pawner good. The safe-keeping fee is calculated on the basis of the pledge as wadi’ah as clearly stated in the brochure scheme by the institution concerned that the scheme is based on the principle of al-qard, al-hassan al-rahn and al-wadi’ah.The purpose of this paper is to determine whether the safe keeping fee (imposed by the financial institutions offering Islamic pawn broking facility in Malaysia) is following the Shariah compliance. A survey has been conducted to Islamic Scholars from various backgrounds using an open ended questions focusing on the safe keeping fee and the operation of the al-rahn system. Based on the findings, it was found that the al-rahn system is acceptable as truly fulfilled the Islamic Shariah in Malaysia by the respondents and by refusing any additional charges or profit taken over and above the safe-keeping fees. This is because any additional charges are considered to be ‘riba’ which is prohibited in Islam based on Al-Quran and Sunnah.